Describing the Fed's conduct with Taylor rules: is interest rate smoothing important? - Efrem Castelnuovo (European Central Bank (ECB), 2003)
In this paper we estimate simple Taylor rules paying particular attention to interest rate smoothing. Following English, Nelson, and Sack (2002), we employ a model in first differences to gain some insights into the presence and significance of the degree of partial adjustment as opposed to a serially correlated policy shock. Moreover, we estimate a nested model to take into account both interest rate smoothing and serially correlated deviations from various Taylor rates prescriptions. Our findings suggest that the lagged interest rate enters the Taylor rule in its own right, and may very well coexist with (usually omitted) variables that relate to asymmetric preferences on the output gap, or financial market indicators. Therefore, while we cannot exclude that serially correlated policy shocks may play a role in describing the federal funds rate path, our results significantly support the importance of the lagged interest rate in Taylor-type models.
Keywords: E4; E5; 330